Secularism and Democracy: A Comparative Study of Turkey and Indonesia - Fauzi, Muhammad Fahmi Basyhah; Asy'ari, Muh. (Universitas Bosowa, 2024)
Turkey and Indonesia, while sharing similarities as Muslim-majority democracies with a presidential system, also exhibit distinct differences. Geographically, Indonesia is located in Southeast Asia, separating the Pacific and Indian Oceans, whereas Turkey serves as a bridge between Asia and Europe. Despite their differences, both countries practice secularism, with Turkey often cited as a successful example of a Muslim-majority state maintaining secular governance. Indonesia, despite its diverse ethnic and religious landscape, also upholds the separation of religion and politics. This paper will explore the practice of secularism in both Turkey and Indonesia, examining its historical background, relationship with democracy, and compatibility with Islam. The first part will cover the concept of secularism, while subsequent parts will focus on the implementation of secularism in Turkey and Indonesia, respectively.